Dangerous (Bonus Story - A Kiss to Remeber) - Palmer, Diana; Simone, Naima (Toronto, Ontario : HQN, 2022)
"Tall, lean and headstrong, FBI agent Kilraven lives by his own rules. And one of those rules includes keeping his hands off Jacobsvilles resident sweetheart, Winnie Sinclair, no matter the temptation. The last thing he wants is to hurt Winnie, whom he fears couldnt handle his haunted past. And this small town may hold not only the woman he fights to resist, but the answers to a cold case that is very personal to Kilraven....Winnie has had her own share of sorrow and senses Kilravens pain. Even though she tries to deny it, the gentle 911 operator feels a connection with the agent. When he makes the disturbing discovery that her familys unsavory past might have a bearing on his case, Winnie is determined to help him crack it...and the ice around his heart."--Back cover.
Keywords: United States -- Federal Bureau of Investigation -- Officials and employees; Fiction; Man-woman relationships -- Fiction; Homicide investigation -- Texas; Fiction; Texas -- Fiction; Romance fiction; Thrillers (Fiction)